The Role of Culturists in Guiding the Local Wisdom Tradition of Pantang Kemali in Adolescents - Mawaddah, Mawaddah; Misrah, Misrah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to describe the role of cultural observers in guiding the Abstinence Kemali local wisdom tradition for adolescents in Kutacane, Southeast Aceh. The research subject MAA (Aceh Traditional Council) and kalak metue kute as humanists who know the cultural of the environment. This research is qualitative research with an ethnographic approach. Conducted in Kutacane, Southeast Aceh with the object of research looking at the role of cultural figures in guiding local wisdom traditions of Pantang Kemali for adolescents. The research data is in the form of the role of cultural observers in guiding local wisdom traditions. The data source was obtained from the local wisdom Pantang Kemali. Data collection techniques were carried out by observation and interviews. While the data analysis was carried out by reducing the data on the role of cultural figures as a whole, presenting data on the role of cultural figures in guiding local wisdom traditions, and drawing conclusions. The study's findings so demonstrate that humanists play a role in steering indigenous wisdom traditions Pantang Kemali in Kutacane through outreach, cultural custom training, and direct reprimands for children who disobey such traditions Pantang Kemali. it is necessary to expand techniques in preserving culture by taking advantage of the progress of the globalization era such as showing existing culture on social media to continue to prioritize national culture to be a priority for young people in the new era of society 5.0.